Religious Metaethics: The Golden Rule for Interfaith Activists in West Java - Dinata, Arfi Pandu; Supriatna, Encup (FISIP UIN SGD Bandung, 2025)
Religion serves as a fundamental source of ethics for its adherents, inspiring social activism. This study aims to explore the role of the golden rule as an ethical foundation in interfaith activism by analyzing how three individuals from different religious backgrounds implement it in their daily lives. Employing a descriptive qualitative approach and the phenomenology of religion method, this research examines the perspectives and religious experiences of the participants regarding the application of compassion values in their social engagements. Data were collected through in-depth interviews with a Buddhist lecturer, a Confucian Sunday school teacher, and a Christian sexual assault victim counselor. The results indicate that all three participants integrate their religious teachings as guiding principles to navigate social, political, and humanitarian challenges. Their activism manifests in various forms, including education, advocacy, and community support, demonstrating that religious values can foster inclusivity and social justice. This study concludes that the golden rule is not merely a universal ethical framework but also a driving force for tangible actions that promote equality and solidarity across different faith communities. Contribution: This study contributes to the understanding of interfaith activism by demonstrating how the golden rule serves as a universal ethical foundation that transcends religious boundaries, fostering inclusivity and social justice through tangible actions.